Redescription and new records of the monotypic genus Trynocoris Herring, 1976 (Heteroptera: Miridae: Cylapinae: Fulviini) - Gorczyca, Jacek; Wolski, Andrzej; Taszakowski, Artur (Zootaxa, 2019)
Trynocoris lawrencei Herring, the only representative of the genus Trynocoris and only known from Barro Colorado Island, Canal Zone, Panama, is recorded for the first time from Mexico, Nicaragua, Panama: Chinqui and Ecuador. Redescription of the genus and species are given along with color photographs of the adults, scanning electron micrographs of selected structures of T. lawrencei. Illustrations of the tarsi and male genitalia are presented for the first time.